EAR PIERCING: A GATEWAY TO TETANUS - Mumtaz, Hassan; Zaman, Nahdia; Zafar, Anam; Saeed, Tariq; Ahmad, Shahzaib (Pakistan Armed Forces Medical Journal, 2022)
Tetanus is initiated by the release of neurotoxins. The progressive paralysis of several muscles is due to contamination of the wound by the toxin. The case under discussion was about a patient with the tetanus infection after ear piercing due to unsterilized instruments and lack of awareness of complications. Due to the late presentation to the hospital, leading to a delay in treatment, the child could not survive. Physicians need to have a vigilant eye to have a high suspicion for tetanus at a very early stage and immediate initiation of advanced critical care, which can favour lifesaving interventions. Prophylactic tetanus toxoid should be administered before any body piercing